Digital tools in secondary chemistry education – added value or modern gimmicks? - Wohlfart, Olivia; Wagner, Alina L.; Wagner, Ingo (Frontiers in Education, 2023)
The article addresses the challenges faced by teachers incorporating digital tools into chemistry education to prepare students for responsible participation in a digital society. Against the background of the Technology Acceptance Model (TAM), the study analyzes the value that chemistry teachers place on digital tools and examines specific factors that influence their implementation in teaching. For this purpose, we conducted and analyzed interviews with 10 secondary school chemistry teachers in Germany. The findings revealed that while subject-specific digital tools were highly valued by teachers, several barriers to their strategic integration exist, including time constraints, high workloads, failing infrastructure, lack of technical support, and a fear of change. The study concludes that subject-specific digital tools have the potential to enhance learning outcomes and recommends teacher training and further education as well as future research to focus on developing and supporting opportunities for teachers to implement subject-specific digital tools to create a more dynamic and engaging learning experiences for students.